Cross‐talk between tumors at anatomically distinct sites. (21st April 2020) - Oliver, Amanda J.; Darcy, Phillip K.; Trapani, Joseph A.; Kershaw, Michael H.; Slaney, Clare Y.
Abstract : Cancer tissue is not homogenous, and individual metastases at different anatomical locations can differ from the primary tumor and from one another in both their morphology and cellular composition, even within an individual patient. Tumors are composed of cancer cells and a range of other cell types, which, together with a variety of secreted molecules, collectively comprise the tumor microenvironment (TME). Cells of the TME can communicate with each other and with distant tissues in a form of molecular cross‐talk to influence their growth and function. Cross‐talk between cancer cells and local immune cells is well described and can lead to the induction of local immunosuppression. Recently, it has become apparent that tumors located remotely from each other, can engage in cross‐talk that can influence their responsiveness to various therapies, including immunotherapy. In this article, we review studies that describe how tumors systemically communicate with distant tissues through motile cells, extracellular vesicles, and secreted molecules that can affect their function. In addition, we summarize evidence from mouse studies and the clinic that indicate an ability of some tumors to influence the progression and therapeutic responses of other tumors in different anatomical locations. Abstract : Tumors are composed of cancer cells and the tumor microenvironment (TME) containing a range of non‐malignant cell types. Cells of the TME can communicate with each other and distant tissues through the circulation, often via secreted molecules and extracellular vesicles (EVs). In this way, a tumor in one location can impact on distal tumors in other locations. This article summarizes the studies that investigate the systemic impact of tumor growth.